Nitrogen fixation and balance in burned versus mulched Mucuna pruriens var. utilis and Pueraria phaseoloides relay maize cropping systems - Hauser, S. (2006)
The contribution of the cover crops Mucuna pruriens var. utilis and Pueraria phaseoloides to the N balance of a sole maize relay cropping system was estimated. Over 4 consecutive years, amounts of N in 8-9 months old aboveground M. pruriens, P. phaseoloides and natural fallow biomass and litter were determined. Fallow biomass was either burned or retained as mulch. Maize aboveground N uptake and N export with grain was determined. The amount of N2-fixed was estimated with the N difference method. In 1998, 1999, and 2000, N content in M. pruriens and P. phaseoloides biomass was higher than in natural fallow. In 2000 and 2001 biomass in previously burned plots contained less N than when biomass had been retained. Fallow-type and biomass management did not interact. Maize N uptake was higher after biomass burning in 1998, yet thereafter higher when biomass was retained. Fallow type had only in 1999 an effect, with highest maize N uptake in the P. phaseoloides system, followed by the M. pruriens system and the natural regrowth. The estimated amounts of N2-fixed were higher in the P. phaseoloidessystem; biomass management had no effect. Nitrogen export with maize grain was highest in the P. phaseoloides system, followed by the M. pruriens system; biomass management had no effect. Maize N uptake into the aboveground biomass and N export with grains was balanced by the amount of N in fallow biomass in all systems when biomass was retained. The amount of N2-fixed did not balance the amount taken up by the maize. In the M. pruriens system the N exported with grains was not balanced by N2 fixation, the P. phaseoloides system had a positive balance of N export in grain versus the amount of N2 fixed.